The Na(+)/H(+) Exchanger Regulatory Factor Stabilizes Epidermal Growth Factor Receptors at the Cell Surface - Lazar, Cheri S. (The American Society for Cell Biology, 2004)
Ligand binding to cell surface receptors initiates both signal transduction and endocytosis. Although signaling may continue within the endocytic compartment, down-regulation is the major mechanism that controls the concentration of cell surface receptors, their ability to receive environmental signals, and the ultimate strength of biological signaling. Internalization, recycling, and trafficking of receptor tyrosine kinases (RTKs) within the endosome compartment are each regulated to control the overall process of down-regulation. We have identified the Na(+)/H(+) exchanger regulatory factor (NHERF) as an important molecular component that stabilizes epidermal growth factor receptors (EGFRs) at the cell surface to restrict receptor down-regulation. The NH(2)-terminal PDZ domain (PDZ 1) of NHERF specifically binds to an internal peptide motif located within the COOH-terminal regulatory domain of EGFR. Expression of NHERF slows the rate of EGF-induced receptor degradation. A point mutation that abolishes the PDZ 1 recognition sequence of EGFR enhances the rate of ligand-induced endocytosis and down-regulation of EGFR. Similarly, expression of a dominant negative mutant of NHERF enhances EGF-induced receptor down-regulation. In contrast to β-adrenergic receptors where NHERF enhances recycling of internalized receptors, NHERF stabilizes EGFR at the cell surface and slows the rate of endocytosis without affecting recycling. Although the mechanisms differ, for both RTKs and G protein-coupled receptors, the overall effect of NHERF is to enhance the fraction of receptors present at the cell surface.